SOCIO-SPATIAL SEGREGATIONS IN SOCIAL MEDIA - Dr. Murat Seyfi,Dr. Ayda Uzunçarşılı Soydaş (Fonseca, Journal of Communication, 2023)
In conjunction with developments in communication technologies, life spaces of people also change and develop. What constitutes the most important building block of these new life spaces are digital communication resources. Digital communication resources form new spaces in social media by manipulating identities and cultures.